2018
DOI: 10.1371/journal.pntd.0006727
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of visceral leishmaniasis in an immunocompetent traveler returning to the United States from Europe

Abstract: A young, healthy traveler returning to the United States presented with fever, night sweats, splenomegaly, and pancytopenia. Bone marrow biopsy revealed leishmaniasis (Leishmania infantum), likely acquired in southern France. Although many cases of endemic visceral leishmaniasis (VL) have been reported in Europe, this is a rare case of imported VL in a healthy traveler returning from Europe to the US. Despite successful initial treatment with liposomal amphotericin B (LamB), relapse occurred. Treatments for VL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In humans, imported cases of both cutaneous and visceral forms of leishmaniasis have been reported in the U.S. A traveler was likely infected in southern France and developed VL upon return to the U.S. [ 63 ]. This traveler had signs such as fever, splenomegaly, and pancytopenia [ 63 ]. Some signs that are reported in human VL cases but rarely in dogs include fever, abdominal pain, and ascites [ 51 ].…”
Section: Disease Manifestations and Implicationsmentioning
confidence: 99%
“…In humans, imported cases of both cutaneous and visceral forms of leishmaniasis have been reported in the U.S. A traveler was likely infected in southern France and developed VL upon return to the U.S. [ 63 ]. This traveler had signs such as fever, splenomegaly, and pancytopenia [ 63 ]. Some signs that are reported in human VL cases but rarely in dogs include fever, abdominal pain, and ascites [ 51 ].…”
Section: Disease Manifestations and Implicationsmentioning
confidence: 99%
“…Histology studies on autopsies from humans, cattle and rodent models, have shown that either by their presence alone, or indirectly due to systemic effects, some of these parasites induce drastic changes in various bone marrow compartments. Reported changes include hypercellular marrow, granulomas, lymphoid nodules, fibrosis and even necrosis in Leishmania infections, all of which correlate with poor prognosis (Haque et al, ; Hellal & Kundu, ; Kumar et al, ). More recently, a murine model of visceral leishmaniasis explored for the first time how CD4+T cell‐mediated immunopathology contributes to repression of medullary erythropoiesis in the bone marrow niche, resulting in affected hematopoietic competence and anaemia – one important sequela of L. donovani infections (Preham et al, ).…”
Section: Primary Lymphoid Organs In Parasitic Infectionsmentioning
confidence: 99%
“…Currently, there is no human vaccine and treatments are expensive, with WHO guidelines recommending the use of just a few drugs, such as Amphotericin B 4 . Over time, several cases of relapses have been documented 5 , 6 , which thus call into question the efficiency of current treatments 5 , 7 and raise the unsolved question of host sites allowing parasite persistence. Indeed, Leishmania has the ability to persist in humans for long periods of time, even after successful treatment 8 .…”
Section: Introductionmentioning
confidence: 99%